Retailing management - Levy, Michael 1950-; Weitz, Barton A. (McGraw-Hill Irwin, 2012)
Retailing is a high tech, global, growth industry that provides challenging and rewarding career opportunities for college graduates. This book and its corresponding tools and exercises were written to expose students to the excitement of retailing and prepare them for a career in retailing and related fields.